Decrease in community antibiotic consumption during the COVID-19 pandemic, EU/EEA, 2020 - Högberg Liselotte Diaz (EUROSURVEILLANCE, 2021)
We present a European Union/European Economic Area-wide overview of the changes in consumption of antibacterials for systemic use (ATC J01) in the community between 2019 and 2020 as reported to the European Surveillance of Antimicrobial Consumption Network. Overall antibiotic consumption decreased by 18.3% between 2019 and 2020, the largest annual decrease in the network's two-decade history. We observed a strong association between the level of community antibiotic consumption in 2019 and the size of the decrease between 2019 and 2020.